Survey and identification of natural enemies of whiteflies in Colombia and Ecuador - LÓPEZ-ÁVILA, ARISTÓBULO; CARDONA-MEJÍA, CÉSAR; GARCÍA-GONZÁLEZ, JAVIER; RENDÓN, FRANCISCO; HERNÁNDEZ, PILAR (Revista Colombiana de Entomología, 2001)
A study was conducted on the survey and identification of natural enemies of the most important species of whiteflies (Homoptera: Aleyrodidae) in various crops and regions of Colombia and Ecuador. The agents with the greatest potential for biological control of the pest. and their geographical distribution were determined. The research was conducted jointly by the International Tropical Agricultura! Center (Clat) and the Colombian Corporation of Agricultura! Research (Corpoica). A total number of 179 sets of data were taken, consisting of biological samples and technical and socioeconomic evaluations. In the survey of parasitoids, whitefly nymphs with symptoms of parasitism were collected and marked and taken to the laboratory for observation until the emergence of adults. The predators observed foraging on different stages o; the pest was collected directly with the help of mouth aspirators. The adults collected were mounted and then identified. The samples of whiteflies infected by entomopathogens were carried in humid chambers to the laboratory, where the pathogens were isolated, purified, and identified. Of the samples were taken in Colombia, Trialeurodes vaporariorum, T. variabilis, Bemisia tabaci (A and B biotypes), B. tuberculata and Aleurotrachelus socialis were identified as the predominant species of whitefly in the crops and areas of study. The natural enemies were identified, as parasitoids the species: Encarsia nigricephala, E. pergandiella, E. formosa, E. hispida, E. strenua, E. minoei, Encarsia sp.. Metaphycus sp.. Eretmocerus californicus, Eretrnocerús sp. (Hymenoptera: Aphelinidae) and Amitus fuscipennis (Hymenoptera: Platygasteridae); as predators: Delphastus pusiitus, Hyperaspis festiva, Delphastus sp., Nephaspis sp. (Coleoptera Coccinellidae) Geocoris sp. (Hemiptera: Lygaeidae), Chrysopa sp. (Neuroptera: Chrysopidae) and some arachnids. The isolations of entomopathogen fungi were identified as Verticillium lecanii, Fusarium sp. and Paecylomices sp .. findings on this study are the first record in Colombia of five species of parasitoids, three of predators and one of entomopathogen fungus as natural enemies and potential biological controllers of whitefly. The other natural enemies reported here had been registered in Colombia and some of them have been evaluated against whiteflies.